An overview of studies at Hacienda San Jose (HSJ) cattle farm - Arango, Jacobo; Matiz Rubio, Natalia; Costa Junior, Ciniro; Bastidas, Mike; Rodriguez, Leonardo; Vázquez, Eduardo; Pérez, Juliana; Ortiz, Daniel; Palacio, Ruben; Idupulapati, Rao; Peters, Michael (2024)
Addressing climate change through collaboration with the agroindustry is highly strategic, given its capacity to influence extensive areas and its significant potential for mitigation.